1978
DOI: 10.1002/bjs.1800650902
|View full text |Cite
|
Sign up to set email alerts
|

Randomized multicentre trial of oral bowel preparation and antimicrobials for elective colorectal operations

Abstract: A study of 120 patients undergoing elective colorectal operations has investigated the effect of adding oral neomycin and metronidazole to bowel preparation in a double-blind randomized controlled trial. Comparisons have also been made between a standard mechanical preparation and the use of an elemental diet. The addition of neomycin and metronidazole to bowel preparation significantly reduced the rate of wound sepsis (P less than 0.01), septicaemia (P less than 0.02) and anastomotic dehiscence (P less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…On the other hand, results of two independent trials in Britain have shown a significant reduction in postoperative sepsis when oral metronidazole was used with kanamycin (Goldring et al 1975) or neomycin (Matheson et al 1978). The present findings support these studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, results of two independent trials in Britain have shown a significant reduction in postoperative sepsis when oral metronidazole was used with kanamycin (Goldring et al 1975) or neomycin (Matheson et al 1978). The present findings support these studies.…”
Section: Discussionsupporting
confidence: 82%
“…The aim of oral antimicrobial therapy is to reduce the bacterial inoculum from within the bowel by lowering the counts of the principal pathogenic bacteria in the faeces rather than providing serum antibiotic levels . It is not surprising, therefore, to find that in the present study the regime of oral metronidazole and placebo neomycin, which has no influence on the faecal flora, was associated with an incidence of sepsis which was similar to that in a control group in a previous trial undertaken in the same hospital (Matheson et al 1978). Comparable results have been reported in a trial to compare the combination of metronidazole and phthalysulphathiazole with phthalysulphathiazole alone (Taylor et al 1979).There was only a reduction in sepsis when both agents were used in combination.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Seven trials were excluded since the first publication, due to several reasons: series of patients 38 ; no control group 39,40 ; data verification in congress 13 ; retrospective study 41 ; case-control study 42 ; study evaluating antimicrobial substances 7 . Four authors of the trials included in our review 14,18,20,24 answered our correspondence and sent data that allowed to stratify anastomoses as colic and low colorectal.…”
Section: Description Of Trialsmentioning
confidence: 99%
“…Since then, several methods of mechanical colon cleansing have been used, via anterograde and/or retrograde routes, which indicates that, so far, no standard mechanical bowel preparation method has been established. Based on some studies [6][7][8] , where the authors clinically investigated the exclusively antibiotic prophylaxis administration in elective colorectal surgery, the importance of stool in the anastomotic area started to be questioned. Reports of emergency surgeries [9][10][11][12] also aroused suspicions regarding the need for mechanical bowel preparation in elective colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%